Is health care financing in Uganda equitable? - Zikusooka, C. M.; Kyomuhang, R.; Orem, J. N.; Tumwine, M. (African health sciences, 2009)
Introduction: Health care financing provides the resources and economic incentives for operating health systems and is a key determinant of health system performance. Equitable financing is based on: financial protection, progressive financing and cross-subsidies. This paper describes Uganda’s health care financing landscape and documents the key equity issues associated with the current financing mechanisms. Methods: We extensively reviewed government documents and relevant literature and conducted key informant interviews, with the aim of assessing whether Uganda’s health care financing mechanisms exhibited the key principles of fair financing. Results: Uganda’s health sector remains significantly under-funded, mainly relying on private sources of financing, especially out-of-pocket spending. At 9.6 % of total government expenditure, public spending on health is far below the Abuja target of 15% that GoU committed to. Prepayments form a small proportion of funding for Uganda’s health sector. There is limited cross-subsidisation and high fragmentation within and between health financing mechanisms, mainly due to high reliance on out-of-pocket payments and limited prepayment mechanisms. Without compulsory health insurance and low coverage of private health insurance, Uganda has limited pooling of resources, and hence minimal cross-subsidisation. Although tax revenue is equitable, the remaining financing mechanisms for Uganda are inequitable due to their regressive nature, their lack of financial protection and limited cross-subsidisation. Conclusion: Overall, Uganda’s current health financing is inequitable and fragmented. The government should take explicit action to promote equitable health care financing by establishing pre-payment schemes, enhancing cross-subsidisation mechanisms and through appropriate integration of financing mechanisms.